Literature Review of the Effectiveness of the Mind Mapping Learning Model on the Science Learning of Class IV Students of SDN Batulaccu - Jusmawati Jusmawati; Perawati Bte Abustang; Inul Aprilia; Yulmianthi Pongnupa; Aldy Syuryo Pranata; Salmawati Salmawati (Universitas Muhammadiyah Enrekang, 2023)
This research aims to analyze the effectiveness of using the Mind Mapping model in science learning. This literature review is used to strengthen the analysis from the various sources used. The literature study in this writing was taken from various data sources related to previously published journals related to the mind mapping model for science learning in elementary schools. Data collection was carried out by tracing data sources from online journals on Google Scholar with journals from the last 5 years. The results that the author obtained from this search were reviewed using analytical descriptive principles. Based on the results of data analysis from various sources, the use of the mind mapping learning model has had a positive impact on science learning with many different improvements in each lesson. Keywords: Learning model; Mınd Mapping learning model; Contextual based learning; Science learning; Elementary school.